Abdominal obesity prevalence in Latin America: a systematic review and meta-analysis comparing ATP III and IDF criteria - Víctor Juan Vera-Ponce; Víctor Juan Vera-Ponce; Joan A. Loayza-Castro; Fiorella E. Zuzunaga-Montoya; Luisa Erika Milagros Vásquez-Romero; Nataly Mayely Sanchez-Tamay; Nataly Mayely Sanchez-Tamay; Juan Carlos Bustamante-Rodríguez; Juan Carlos Bustamante-Rodríguez; Jhosmer Ballena-Caicedo; Jhosmer Ballena-Caicedo; Carmen Inés Gutierrez De Carrillo; et al. (Frontiers in Endocrinology)
BackgroundAbdominal obesity (AO) represents a significant cardiovascular risk factor with distinctive characteristics in Latin American populations. Its prevalence has increased substantially in recent decades, although estimates vary according to the diagnostic criteria.ObjectiveTo determine the prevalence of AO in Latin American populations through a systematic review with meta-analysis, comparing ATP III and IDF criteria.MethodsA systematic search was conducted across SCOPUS, Web of Science, PubMed, and EMBASE databases. Observational studies evaluating AO prevalence in Latin American populations using either ATP III (≥102/88 cm) or IDF (≥90/80 cm) criteria were included. Meta-regressions were performed to assess the influence of publication year and sample size.ResultsSixty-one studies were included (n=281,694 participants). The pooled prevalence according to ATP III criteria was 40% (95% CI: 34-46%) and 62% (95% CI: 56-68%) according to IDF criteria. Sex-stratified analysis revealed significantly higher prevalences in women (ATP III: 50% vs 27%; IDF: 74.3% vs 46.8%). Temporal meta-regression demonstrated an upward trend, particularly in studies utilizing IDF criteria, while sample size showed no significant influence on prevalence estimates. Substantial geographic variations were observed, with Mexico and Venezuela exhibiting the highest prevalences. Heterogeneity was considerably high (I²>99%) across all analyses.ConclusionsAO prevalence in Latin America is high and demonstrates significant sexual dimorphism. These findings challenge the validity of current cut-off points and suggest the need to develop Latin American-specific criteria based on clinically relevant outcomes.